Some vocational guidance issues in general education schools of the Soviet Social Republic of Lithuania - Kregždė, S. (Psichologija, 1962)
According to the experimental material collected during the survey of fourteen rural and urban schools, with participation of 467 students of 9th, 10th, and 11th grades by using a questionnaire, lesson monitoring, conversations with students and teachers, and other methods, an insufficient determination on the future profession choice becomes obvious among the students of senior grades. Most (68.52%) students point out that they scarcely know the chosen profession. Nevertheless, the majority of seniors (91.22%) intend to enter higher education and specialized secondary education institutions. The majority of just a small group of students who intend after graduation to go straight to work in production (8.78%), explain their choice anything but the significance of their chosen profession to the society. They seek not a deeper understanding of life, but to accumulate the experience required for entrance to a higher education institution. The motives of the majority willing to study further are of a public character. Experimental materials show that up till now this issue has not been solved in vocational classes either. Just a small part of students studying in these classes are planning to work according to the profession acquired at school or enter a relevant higher education school. Based on that, the article suggests the ways to improve vocational guidance which should both correspond to the needs of national economy and consider the individual inclinations of students and their other personal qualities. For systematic and scheduled vocational guidance, certain coordination should be performed by schools, soviet districts and party organizations. Management and directive centers are necessary to implement not only practical but research work as well.